2020
DOI: 10.1007/s11085-020-10003-w
|View full text |Cite|
|
Sign up to set email alerts
|

On the High-Temperature Oxidation Behavior of a Ta-Containing Quaternary Co-Base Model Alloy System with γ/γ′-Microstructure - Influence of γ′-Volume Fraction, Surface State, and Heating Condition on Alumina Growth

Abstract: The improvement of the high-temperature oxidation resistance remains an ambitious goal for the design of new γ/γ′-strengthened Co-base superalloys, since their oxidation resistance beyond 800 °C still ranks behind their Ni-base counterparts. To better understand the origin of the poor oxidation resistance at higher temperatures, this study focuses on early stages of oxidation of four quaternary (Co-Al-W-Ta system) Co-base model alloys with a two-phase γ/γ′-microstructure and varying γ′-volume fraction at 800 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…In contrast, all alloys in polished surface state were prone to exceptionally high oxidation kinetics caused by massive internal oxidation and external growth of Co oxides. In accordance with other authors, it was concluded that shot-peening-and by that plastic deformation-induces additional lattice defects that can act as short circuit paths for diffusion and thereby increase the effective solute diffusivity [18][19][20][21].…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…In contrast, all alloys in polished surface state were prone to exceptionally high oxidation kinetics caused by massive internal oxidation and external growth of Co oxides. In accordance with other authors, it was concluded that shot-peening-and by that plastic deformation-induces additional lattice defects that can act as short circuit paths for diffusion and thereby increase the effective solute diffusivity [18][19][20][21].…”
Section: Introductionsupporting
confidence: 88%
“…When the exposure procedure abstained from heating in argon atmosphere, for shot-peened samples clearly less continuous and protective alumina scales with higher amounts of transient oxides developed [18]. In contrast, for polished samples, no significant effect of the heating atmosphere on oxidation kinetics was found [18].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations